The changes in transformation temperatures under stress of Cu-12.7Al-5Ni-2Mn alloy - Zengin, R; Ceylan, M (Elsevier, 2004)
The effects of the stress on shape memory properties Of Cu-12.7Al-5Ni-2Mn shape memory alloy have been investigated. Applied stress increases transformation temperatures and the relationship between T-0, temperature at which Gibbs free energy of austenite equals that of martensite, and plastic deformation is linear. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: shape mernory; pressure; austenitic-martensitic phase transitions; Gibbs free energy